Characterization of Natural Fiber Reinforced Resin Composites and Glass Waste Powder for Brake Linings - Sudarma, Andi Firdaus; Fitri, Muhamad (Graduate School of Syiah Kuala University, 2025)
Currently, there are two types of brake linings in the market: asbestos brake lining and asbestos-free brake linings. The asbestos Brake lining was widely used due to durability, heat resistance and friction properties. In terms of price, asbestos brake linings are indeed cheaper than asbestos-free brake linings, However, they have negative impact on the environment and human health. In high enough concentrations, asbestos dust can cause Mesothelioma, a malignant tumor in the lining of the lungs). Therefore, it is necessary to find a substitute material for asbestos that is affordable but possesses similar characteristics to asbestos brake linings. While, the high production of salak in Indonesia has a side effect, i.e.: the large volume of waste in the form of peel and seeds of salak. If not utilized, of course this will become waste. Meanwhile, glass waste is an inorganic waste material that is very difficult to decompose and pollutes the environment. Meanwhile, glass waste is one of the inorganic waste materials that is very difficult to decompose and pollutes the environment. The aim of this study was to characterize composite resin materials reinforced with glass waste powder, Snake Fruit Peel Powder and teak wood sawdust as alternative brake lining materialsThe research was conducted through laboratory experiments, beginning with the manufacture of sample specimens, followed by measuring their density, hardness, and friction coefficient testing then compared to brake lining on the market and also based on the SNI 09-0143-1987 standard. The result showed, some of the investigated samples in this study meet the reqirement of SNI 09-143-1987, where the lowest Brinell Hardness number of the sample 120.33. There are 5 specimens of friction coefficient of the specimens are also fullfill the requirement.